2010
DOI: 10.21432/t2c01s
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Graphical Literacy through Knowledge Building

Abstract: This study examined growth in graphical literacy for students contributing to an online, multimedia, communal environment as they advanced their understanding of biology, history and optics. Their science and history studies started early in Grade 3 and continued to the end of Grade 4; students did not receive instruction in graphics production, nor were they required to produce graphics. Results show that students spontaneously produced graphics that advanced along seven dimensions, including effective repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, these findings are mostly consistent with relevant previous studies. It is frequently cited in the literature (Fry, 1981;Gan et al, 2010;Ludewig, 2018;Shah & Hoeffner, 2002;Wainer, 1992) that presenting information in a visual form, such as graphs, is more understood and usually preferred by the people. Also, after a study with a large secondary school student sample, Yinkang and Yoong (2007) reported that students held neutral to positive views about the statistical graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings are mostly consistent with relevant previous studies. It is frequently cited in the literature (Fry, 1981;Gan et al, 2010;Ludewig, 2018;Shah & Hoeffner, 2002;Wainer, 1992) that presenting information in a visual form, such as graphs, is more understood and usually preferred by the people. Also, after a study with a large secondary school student sample, Yinkang and Yoong (2007) reported that students held neutral to positive views about the statistical graphs.…”
Section: Discussionmentioning
confidence: 99%
“…Fry (1981) has made one of the first definitions of graph literacy, as the skills for reading and drawing graphs. Gan, Scardamalia, Hong, and Zhang (2010) defined it as the ability to create, prepare, present, read, and interpret graphs. Friel and Bright (1995) made their graph literacy definition based on three levels: reading the data (reading the visible values in the graph), reading between the data (explaining the general information in the graph), and reading beyond the data (making comments and inferences about the graph).…”
Section: Graph Literacymentioning
confidence: 99%
“…Research also suggests that stories about scientists' struggles during their knowledge building processes can be useful in improving students' understanding of how scientific theories are conceptually related to one another (Hong and Lin-Siegler 2012;Klassen and Klassen 2014). Prior research concerning knowledge building practice suggests that it is useful in enhancing student learning in various subject areas, for example, science learning (Hakkarainen 2004;Scardamalia and Bereiter 1991), mathematics learning (Moss and Beatty 2006), language learning (Sun et al 2010), and graphical literacy (Gan et al 2010). Furthermore, studies also indicate that knowledge building activities enhance students' general epistemological understanding (Hong and Lin 2010;Hong et al 2011).…”
Section: The Present Studymentioning
confidence: 99%
“…This requirement points to the importance of the concept of graphical literacy. The concept of graphical literacy is expressed in various ways (Bursal & Polat, 2020;Delport, 2021;Friel et al, 2001;Fry, 1981;Galesic & Garcia-Retamero, 2011;Gan et al, 2010;Ozmen et al, 2020). Bursal and Polat (2020) define graphical literacy as the ability to determine the type of graph appropriate for the context, to convert between different graphs, and to comment on these changes regarding data in the graph.…”
Section: Introductionmentioning
confidence: 99%